2015
DOI: 10.1785/0120140285
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Analysis of Seismic Moment Tensor at The Geysers Geothermal Field, California

Abstract: The Geysers geothermal field is one of the most seismically active regions in northern California. Most of the events occur at shallow depths and are related to stress and hydrological perturbations due to energy production operations. To better understand the relationships between seismicity and operations, better source mechanism information is needed. Seismic moment tensors offer insight into the nature of equivalent forces causing the seismicity. Fifty-three M >3 events located at The Geysers geothermal fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 59 publications
(81 reference statements)
6
23
0
Order By: Relevance
“…Retrieved mechanisms with positive volumetric components agree well with observations of Boyd et al (2015). However, these results are unexpected in a region that is undergoing volumetric contraction, as determined in geodetic studies.…”
Section: 1002/2017jb014897supporting
confidence: 82%
See 3 more Smart Citations
“…Retrieved mechanisms with positive volumetric components agree well with observations of Boyd et al (2015). However, these results are unexpected in a region that is undergoing volumetric contraction, as determined in geodetic studies.…”
Section: 1002/2017jb014897supporting
confidence: 82%
“…Kirkpatrick et al (1996) used P and S wave amplitudes and polarities to obtain MT solutions for 2,552 events. Most recent studies using waveform data have found even larger ISO components (up to 47%) for certain earthquakes (Boyd et al, 2015;Johnson, 2014b). The ISO parts were up to 30% of the mechanism and had both positive and negative signs.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Several studies focusing on the source mechanisms of small groups of events (15-53 events) of larger magnitudes (M > 3.0) and/or with limited spatial distributions were reported using either local short-period or regional broadband networks (Boyd et al, 2015;Guilhem et al, 2014;L. R. Johnson, 2014aL.…”
Section: Introductionmentioning
confidence: 99%